Phylogenetic Analysis of HA and NA Genes of Swine Influenza Viruses in Serbia in 2016-2018 - Maksimović Zorić Jelena (Sciendo, 2020)
Pigs are very important for the epidemiology of influenza A viruses, being commonly infected with the lineages of most adapted H1N1, H3N2, H1N2 swine subtypes. Epidemiological complexity of swine influenza is increasing by a periodic spillover of human or avian viruses in the pig population when genetic shifts can occur. The objectives of this research were to determine the presence of the influenza A virus in nasal and tracheobronchial swabs and lung tissue samples of ill and dead pigs on commercial farms, to determine circulating subtypes and characterize them through the phylogenetic analysis of hemagglutinin (HA) and neuraminidase (NA) genes. A total of 255 samples collected from 13 farms were analyzed by means of real-time RTPCR. The genome of influenza A virus was detected in 24 samples, which represented a 61.5% prevalence at the farms level (influenza A virus was confirmed in 8 out of 13 farms included in this study). Based on HA and NA gene sequences of 8 viruses, the circulation of H1N1 and H3N2 subtypes of influenza A viruses were determined. In addition, one farm exhibited a time separated circulation of H1N1 and H3N2 virus subtypes. Using Influenza Research Database, our viruses of the H1 subtype were classified into 1C.2.1 and 1A.3.3.2. clade. Based on the nucleotide sequences of HA genes, three viruses of the H1N1 subtype belong to the H1N1pdm09 lineage, and the other four to Eurasian “avian-like” H1avN1 lineage; while based on NA genes sequences, these seven viruses belong to Eurasian “avian-like” H1avN1 lineage. Both HA and NA genes of the virus of the H3N2 subtype belonged to the A/swine/ Gent/1/1984-like H3N2 lineage.